Hotel management and operations - Rutherford, Denney G (John Wiley, 2015)
"Hotel Management and Operations, Fourth Edition helps readers develop the wide-ranging knowledge and analytical skills they need to succeed in today's burgeoning and dynamic hotel industry. This comprehensive volume encourages critical thinking by providing different points of view through contributions from sixty leading industry professionls and academics. Within a coherent theoretical structure, this updated Fourth Edition enables readers to formulate their own ideas and solutions." "Complete with extensive references and suggestions for further reading, Hotel Management and Operations, Fourth Edition is an ideal book for university hospitality programs and management training programs within the hotel industry."--Jacket.